MOISTURE SORPTION ISOTHERM CHARACTERISTICS OF AWARA FOOD (FUDMA JOURNAL OF SCIENCES, 2020)
Moisture sorption and storage stability of Awara were evaluated using gravimetric method. Guggenhein-Anderson-de boer (GAB) and Brunauer Emmett and Teller (BET) were used in evaluating sorption and desorption isotherm at temperature range of 30, 40 and 50oc in the range of water activity (0.1-0.9).Sigmoid moisture isotherm shapes were obtained at various temperatures. Lowest level EMC was obtained at highest temperature (500c).A non-linear regression analysis was used to fit both BET and GAB. GAB was found to generate higher coefficient of determination R2 (0.9986, 0.9959 and 0.9933) and lowest mean of relative percentage p% (0.231, 0.0061 and 0.0017) at temperature range (30, 40 and 500c) respectively. Safe % water and storage stability were all predicted from adsorption isotherm curve. 3.14, 3.19 and 3.10 were found to be the safe % water which corresponds to the 3.8aw for GAB adsorption graphs at 30, 40 and 500c temperatures respectively. This safe % water will be useful in packaging and determination of shelf- life of Awara.
Keywords: Awara, sorption isotherm, BET and GAB models, water activity